Sudden unexpected death after initial infusion of rituximab for Waldenström macroglobulinemia/lymphoplasmacytic lymphoma: an autopsy case - Shojiro Ichimata; Yukiko Hata; Kazuhiro Nomoto; Tsutomu Sato; Naoki Nishida (BMC, 2024)
Abstract Background Waldenström's macroglobulinemia (WM) is defined as a lymphoplasmacytic lymphoma (LPL) involving the bone marrow (BM) with presence of IgM monoclonal protein, and comprises > 95% of all LPL cases. Rituximab-based regimens have been predominant in the management of WM. Infusion-related reactions (IRRs) are a primary concern with rituximab, although it is generally better tolerated with less toxicity than conventional anticancer agents. Here, we present an autopsy case of an elderly man who died suddenly after receiving the initial infusion of rituximab for WM/LPL. Case presentation An 84-year-old man was found dead in his bedroom. He had undergone the initial intravenous rituximab infusion for progressive anemia related to Waldenström's macroglobulinemia/lymphoplasmacytic lymphoma (WM/LPL) approximately 15 h before death. Although the protocol for rituximab administration and additional medication was considered appropriate, he exhibited several symptoms consistent with infusion-related reactions (IRRs) during the infusion. Autopsy revealed monotonous proliferation of small-to-medium-sized lymphocytic cells in the bone marrow, consistent with the premortem diagnosis of WM/LPL. Additionally, immunoglobulin λ-light chain-derived amyloid (ALλ) deposition was identified in all organs other than the brain. Although ALλ deposition and LPL infiltration were found in the heart, they were not severe enough to cause severe functional impairment. Severe congestion and/or edema were observed in the lungs, liver, and brain. Although significant inflammatory cell infiltration was not found in any organs, laboratory tests revealed elevated serum levels of inflammatory cytokines, including interleukin-1β, interleukin-6, tumor necrosis factor-α and the presence of IgM-λ monoclonal protein. Conclusion Acute IRRs associated with the initial rituximab infusion were the major contributing factor to his sudden unexpected death. The autopsy findings of present case suggest the necessity for thorough monitoring of older patients with WM/LPL undergoing rituximab treatment, particularly when pronounced IRRs occur during the first administration, in addition to investigating complications of WM/LPL before infusion.